Knowledge and vaccination acceptance toward the human monkeypox among men who have sex with men in China - Zheng, Min; Qin, Chenyuan; Qian, Xiaohan; Yao, Yongming; Liu, Jue; Yuan, Zhi; Ma, Lin; Fan, Jiacheng; Tao, Rui; Zhou, Feng; Chen, Wenyan; Zhu, Zhilin; et al. (Frontiers in Public Health, 2022)
Background MSM individuals are at high risk of monkeypox infection, and judicious use of vaccines can control the outbreak. Therefore, we conducted a national cross-sectional survey to assess the vaccination willingness, associated factors, and related knowledges of monkeypox among MSM individuals in China. Methods This anonymous cross-sectional study was conducted in China from July 1 to July 3, 2022, and electronic questionnaires were sent online to MSM individuals of specific institutions. Men, aged 18 or older, who had anal sex in the past year were recruited. Multivariable logistic regression models and univariable logistic regression models were performed in different groups of participants, including all eligible respondents, people with or without self-reported HIV infection, and people who had sex with at least one male sexual partner in last month. Results A total of 2,618 male respondents, including 2,134 homosexuals and 484 bisexuals, were enrolled in our final analysis. Most of the respondents had a certain understanding of the source of infection, transmission route, and preventive measures, but lacked knowledge of the susceptible population, clinical manifestations, vaccination, and treatment. In total, 90.2% of all respondents were willing to receive the vaccines against monkeypox. Among people with self-reported HIV infection, the vaccination acceptance rate was 91.7%, while it was 89.7% in the rest. The main influencing factors were knowledge about monkeypox (moderate: aOR = 1.47, 95% CI: 1.04–2.08; high: aOR = 2.03, 95% CI: 1.23–3.34), knowledge about prevention measures (moderate: aOR = 3.52, 95% CI: 2.51–4.94; high: aOR = 5.32, 95% CI: 2.98–9.47), concerns about their susceptibility to monkeypox infection (aOR = 4.37, 95% CI: 3.29–5.80), and possible contact with people and animals in epidemic areas (aOR = 0.42, 95% CI: 0.25–0.70). For self-reported HIV-infected individuals, education (bachelor degree: aOR = 0.40, 95% CI: 0.18–0.89) and poor condom use (sometimes: aOR = 2.18, 95% CI: 1.06–4.47) may also affect the vaccination. Conclusions There was still a lack of knowledge about the human monkeypox among MSM individuals in China. The vaccination acceptance rate of this high-risk population was high, and it was closely related to the knowledge factors, fear of infection, and possible contact with people or animals in affected areas. Targeted publicity and education of the high-risk groups, vaccination pre-arranged planning should be formulated to cope with the further development of this infectious disease.